The Role of Central Banks in Stabilizing Financial Markets: Lessons from Recent Crises - Rai, Devendra Kumar (Kanakai Journal, 2024)
Central banks play a pivotal role in stabilizing financial markets during economic crises through liquidity support, unconventional monetary policies, and macroprudential regulation. This study explores the strategies employed by central banks during two major financial crises—the 2008 global financial crisis and the COVID-19 pandemic. Using a comparative case study approach, it examines the effectiveness of interventions such as lender-of-last-resort functions, quantitative easing (QE), and regulatory measures aimed at mitigating systemic risks. The findings reveal that liquidity support and emergency lending facilities were crucial in preventing bank collapses, while QE helped restore investor confidence by lowering long-term interest rates and encouraging investment. However, the study also highlights concerns about the long-term risks associated with unconventional monetary policies, including potential financial imbalances and moral hazard. Additionally, it discusses the growing role of macroprudential regulation in enhancing financial stability. Despite the success of central bank interventions in mitigating crises, the research points to the need for further studies on their long-term impacts, especially regarding financial stability, central bank independence, and governance. The expanded role of central banks remains a critical focus for policymakers as they navigate future economic challenges.